A study on the epidemiology of tinnitus in the United Kingdom - Stohler, Nadja A (Clin Epidemiol, 2019)
PURPOSE: Subjective tinnitus is a common symptom with potentially negative impact on quality of life. More research is required to gain a deeper understanding of the disease and its clinical presentation. To estimate the incidence of tinnitus and to describe patient-related characteristics such as lifestyle factors and comorbidities. PATIENTS AND METHODS: Using the Clinical Practice Research Datalink, we calculated incidence rates of first-time diagnosed tinnitus in an adult population between 2000 and 2016. We stratified incidence rates by sex, age, and year of diagnosis. Additionally, we performed a 1:1 matched case-control study comparing body mass index, lifestyle factors and selected comorbidities between patients with incident tinnitus and tinnitus-free controls. RESULTS: We identified 109 783 adults with a first-time diagnosis of tinnitus between 2000 and 2016, yielding an overall age-standardized incidence rate of 25.0 new tinnitus cases per 10,000 person-years (95% CI: 24.6–25.5). There was a steady increase in tinnitus incidence throughout the study period. Approximately 80% of tinnitus cases were diagnosed at age 40 years or older. We observed the highest incidence rate in individuals aged 60–69 years (41.2 per 10,000 person-years, 95% CI: 40.7–41.7). Smokers and alcohol drinkers were at lower risk of being diagnosed with tinnitus compared with non-smokers and non-drinkers, respectively. The occurrence of tinnitus was strongly associated with a recent diagnosis of several otological and vestibular disorders as well as head and neck disorders. CONCLUSION: The present observational study found an increasing incidence of tinnitus over time, emphasizing the continuously growing health burden. The findings on patient characteristics, lifestyle factors, and selected comorbidities contribute to a better understanding of risk factors for tinnitus.